Analysis of Variations in Sharia Economic Dispute Resolution System - Nurhikmah, Aulia; Madani, Farid; Ridwan, Ahmad Hasan; Bisri, Hasan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This research aims to examine in depth these normative foundations and their implications for the practice of sharia economic dispute resolution in Indonesia. The success of the development of a national Islamic financial system is highly dependent on the effectiveness of dispute resolution mechanisms, so it is important to examine how Islamic law and positive law offer different but complementary approaches. This study uses a qualitative method with a literature study approach to explore developing dispute resolution models. The findings of the study show that in the perspective of Islamic law, the settlement of sharia economic disputes can be carried out through two main models: through judicial authority (qaḍā') and outside the judiciary (taḥkīm or ṣulḥ). Meanwhile, within Indonesia's positive legal framework, there are two main approaches, namely: (1) dispute resolution through litigation processes in judicial institutions, and (2) dispute resolution through non-litigation mechanisms outside of court, such as mediation, arbitration, or other forms of ADR. This study confirms that the diversity of dispute resolution models provides flexibility as well as challenges in efforts to realize justice and legal certainty in sharia economic practices in Indonesia.